ANALISIS STRUKTURAL FUNGSIONAL PERAN BALAI EKONOMI DESA (BALKONDES) TUKSONGO DALAM PENGEMBANGAN DESA WISATA BERBASIS PARIWISATA BERKELANJUTAN - Lokeswara, Akhlis Dzakira; Trinugraha, Yosafat Hermawan; Pudyastuti, Septina Galih (Jurnal Dinamika Sosial Ekonomi, 2024)
Indonesia is an archipelagic country with a variety of natural and cultural resources. Tourism is a rapidly growing sector in Indonesia. Village economic center is proof of rapid development in the tourism sector. Tuksongo village economic center is one of 20 Village economic center in the area around Borobudur Temple. It is hoped that the construction of village economic center will be an economic showcase for the village community. This research aims to describe the role of Village economic center Tuksongo in developing a tourist village based on sustainable tourism. This research uses a qualitative approach. The sampling technique used was purposive sampling. Data collection was carried out by interviews, observation and documentation. The validity of the data used in this research is source triangulation. Analysis of the role of village economic center in the development of sustainable tourism-based tourist villages was carried out using the Theory of Structural Functionalism by Talcott Parsons. The results of the research show that the Tuksongo Balai ekonomi desa plays an important role in the development of tourist villages in Tuksongo Village. The development carried out by village economic center uses the principle of sustainability and fulfills three important aspects, namely socio-cultural, economic and environmental aspects. The functions of adaptation, goal attainment, integration and latency are carried out well by Balcondes in developing tourist villages.